Isolasi, Karakterisasi, Dan Aplikasi Nanokristal Selulosa : Review - Nina Hartati; Edi Kurniawan; Meyci Trisna; Intan Noviarni (Fakultas Sains dan Teknologi, UIN Sulthan Thaha Saifuddin Jambi, 2023)
Cellulose nanocrystals are a type of cellulose with a nanometer size. Sources of cellulose nanocrystals can come from plants, tunicates, or bacteria. Agricultural wastes have great potential as a source of cellulose nanocrystals. Methods that can be used to isolate cellulose nanocrystals from the main ingredient are hydrolysis methods involving the use of organic acids, enzymatic hydrolysis methods, mechanical treatment methods, or a combination of these methods. Each method has its own advantages and disadvantages. Cellulose nanocrystals have been extensively researched and applied in various fields ranging from reinforcing agents in polymer matrices, playing a role in drug delivery systems, or other polymeric materials. This review provides information on each of the isolation methods and applications of these cellulose nanocrystals. Keywords: Cellulose Nanocrystals, Hydrolysis, Mechanical Treatment.